Physical and economic impacts of sedimentation on fishing activities Nam Pong Basin, Northeast Thailand - Johnson, S. H.; Kolavalli, Shashidhara (1984)
Using aerial and LANDSAT data a dynamic model of the Nam Pong Basin in Northeast Thailand has been developed. The model simulates erosion that results from conversion of watershed land to alternative uses. Erosion values are passed to a linked reservoir model where they are converted to turbidity levels. Operated together the two models document that annual economic returns have declined by 209000; 100/year for km 2 clearcut and 66/year for new fishermen. Simulation of alternative management scenarios predicts continued increases in sedimentation. Restrictions on number of fishing families and protection of critical watershed areas are necessary to protect the long-term sustainability of the reservoir fish production system.
Photocopy.
Includes bibliographical references (page 188).
DOI: 10.1080/02508068408686537.
Keywords: Agriculture -- Asia, Southeast -- Thailand, Northeast; Economic conditions -- Asia, Southeast -- Thailand, Northeast